Threshold dynamics for a Tuberculosis model with seasonality - Xinli Hu (Mathematical Biosciences and Engineering)
In this paper, we investigate a SEILR tuberculosis model incorporating the effect of seasonal fluctuation, where the loss of sight class is considered. The basic reproductionnumber $R_{0}$ is defined. It is shown that the disease-freeequilibrium is globally asymptotically stable and the diseaseeventually disappears if $R_{0}1$. Numerical simulations are provided to illustrate analytical results.